A modified phenomenological model for PAAm hydrogel with hardening effect under cyclical loading - Goh, Jing Xuan (Nanyang Technological University, 2023)
In this study, an improvement is suggested upon existing phenomenological models to more accurately reflect the Mullins effect, strain hardening phenomenon, and residual stretch associated with PAAm hydrogel. Our modifications to existing research allowed for better predictions of hydrogel fatigue fracture behaviour, which has important implications for the durability and reliability of hydrogel-based technologies. The root mean square value improved by 69% in comparison to the model proposed by Wang [1]. This work attempts to create the best model for capturing the stress-stretch characteristic of PAAm hydrogel over a prolong cycle.